Attributable clinical and economic burden of carbapenem-non-susceptible Gram-negative infections in patients hospitalized with complicated urinary tract infections. Issue 1 (May 2019) - Tabak, Y.P.; Sung, A.H.; Ye, G.; Vankeepuram, L.; Gupta, V.; McCann, E.
Summary: Background: Gram-negative complicated urinary tract infections (cUTIs) can have serious consequences for patients and hospitals. Aim: To examine the clinical and economic burden attributable to Gram-negative carbapenem-non-susceptible (C-NS; resistant/intermediate) infections compared with carbapenem-susceptible (C-S) infections in 78 US hospitals. Methods: All non-duplicate C-NS and C-S urine source isolates were analysed. A subset had principal diagnosis ICD-9-CM codes denoting cUTI. Collection time (<3 vs ≥3 days after admission) determined isolate classification as community or hospital onset. Mortality, 30-day re-admissions, length of stay (LOS), hospital cost and net gain/loss in US dollars were determined for C-NS and C-S cases, with the C-NS-attributable burden estimated through propensity score matching. Three subgroups with adequate patient numbers were analysed: cUTI principal diagnosis, community onset; other principal diagnosis, community onset; and other principal diagnosis, hospital onset. Findings: The C-NS-attributable mortality risk was significantly higher (58%) for the other principal diagnosis, hospital-onset subgroup alone (odds ratio 1.58, 95% confidence interval 1.14–2.20; P  < 0.01). The C-NS-attributable risk for 30-day re-admission ranged from 29% to 55% (all P  < 0.05). The average attributable economic impact of C-NS was 1.1–3.9 additional days LOS (all P  < 0.05), US$1512–10, 403 additional total cost (all P  < 0.001) and US$1582–11, 848 net loss (all P  < 0.01); overall burden and C-NS-attributable burden were greatest in the other principal diagnosis, hospital-onset subgroup. Conclusion: Greater clinical and economic burden was observed in propensity-score-matched patients with C-NS infections compared with C-S infections, regardless of whether cUTI was the principal diagnosis, and this burden was most severe in hospital-onset infections.